Application of the double bounded dichotomous choice model to the estimation of parent's willingness to pay for the hand foot mouth disease vaccination: a survey in Selangor, Malaysia - Rajamoorthy, Yogambigai; Mohd Taib, Niazlin; Harapan, Harapan; Wagner, Abram Luther; Munusamy, Subramaniam (Public Library of Science, 2023)
Hand foot and mouth disease (HFMD) is a notifiable viral disease in Malaysia, and is transmitted primarily among young children. Although vaccines for enteroviruses 71 (EV-71) were approved in China against HFMD, the availability and the acceptance of the vaccine in the Malaysia are unknown. This study investigated and ascertained the determinants of willingness-to-pay (WTP) for HFMD vaccination in Selangor Malaysia. This study adopted a cross-sectional, contingent valuation method involving 390 parents of young children aged six and below. The double bounded dichotomous choice (DBDC) approach was employed to assess the WTP for HFMD vaccine among respondents. A bivariate probit model was used to assess the key determinants of WTP for HFMD vaccine, while the mean WTP was measured using the Krinsky and Robb procedure. We found that 279 (71.5%) of parents were willing to pay for the HFMD vaccination. The estimated single bounded mean WTP was MYR460.23 (equivalent to US$ 102.17) for two doses of HFMD vaccination. The double bounded analysis revealed that the vaccine’s price, poor education background and lower income were the key factors that significantly affected the WTP, with the estimated mean WTP being MYR394.00 (US$ 87.47). In conclusion, most Malaysian parents are willing to pay for the HFMD vaccination. The estimated WTP identifies the optimal price point for HFMD vaccination in Malaysia. Furthermore, the government should focus on an awareness programme for the HFMD vaccination among parents who have lower income or education level.